2019
DOI: 10.1002/ejp.1398
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life change in patients treated at a multidisciplinary pain clinic

Abstract: Background Multidisciplinary pain management (MPM) is a generally accepted method for treating chronic pain, but heterogeneous outcome measures provide only limited conclusions concerning its effectiveness. Therefore, further studies on the effectiveness of MPM are needed to identify subgroups of patients who benefit, or do not benefit, from these interventions. Our aim was to analyse health‐related quality of life (HRQoL) changes after MPM and to identify factors associated with treatment outcomes. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 48 publications
4
18
0
Order By: Relevance
“…Importantly, although our results showed positive effects at a group level, data on our MCID indicated that around 20% of the patients deteriorated at least one MCID on the primary and secondary outcomes, and that is despite receiving IMPR. This is in line with recent findings from Vartiainen et al [ 43 ], who also showed that while health-related quality of life was improved in nearly half of the patients, there were also approx. 30% who reported a clinically important deterioration at 12-month follow-up after rehabilitation.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, although our results showed positive effects at a group level, data on our MCID indicated that around 20% of the patients deteriorated at least one MCID on the primary and secondary outcomes, and that is despite receiving IMPR. This is in line with recent findings from Vartiainen et al [ 43 ], who also showed that while health-related quality of life was improved in nearly half of the patients, there were also approx. 30% who reported a clinically important deterioration at 12-month follow-up after rehabilitation.…”
Section: Discussionsupporting
confidence: 93%
“…More specifically, the results showed that low physical functioning, low health-related quality of life, high life interference and long duration of pain before MMRP seemed to affect women more than men in relation to sick leave 1 year after MMRP. This is in line with previous research that has shown that health-related quality of life [43] and physical disabilities [45] can have an impact on the possibility of a successful return to work.…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate the urgency to offer early interventions to persons with chronic pain in need of multimodal rehabilitation. These findings should be viewed in light of previous research which has presented links between long pain duration and less positive treatment outcomes regarding health-related quality of life [43] as well as return to work, after multimodal pain rehabilitation [44].…”
Section: Discussionmentioning
confidence: 55%
“…In patients with chronic musculoskeletal pain, multidisciplinary or interdisciplinary pain rehabilitation either improved HRQOL, or it did not [ 10 , 11 , 12 , 13 , 14 ]. However, major improvement in HRQOL after pain rehabilitation programs positively associated with shorter duration of pain and worse baseline HRQOL [ 15 ]. Similarly, two years after participating in a pain program for patients with mixed chronic musculoskeletal pain, improvements in pain and function were maintained, health-care usage decreased, and the number of working hours increased [ 16 ].…”
Section: Introductionmentioning
confidence: 99%